ANALYSIS OF FINANCIAL AGROINDUSTRY JIPANG : (Case Study of UMKM Sinar Abadi in Jeblog Village, Talun, Blitar) - Naila Nafiatul Hayati (Universitas Islam Balitar, 2018)
A business feasibility analysis is needed to see a picture of feasible or tudak, In running japan business agroindustry, most entrepreneurs have not done a special financial recording for his business, so it is not known how much it will cost and income on his business. This study aims to determine the amount of expenses, income received and profits, knowing business feasibility and knowing the length of capital jipang agro industry in UMKM Sinar Abadi can be back in units of time year. Method analysis used in business feasibility analysis include R / C Ratio, Net Present Value (NPV), Break Event Point (BEP), and Pay Back Period (PP). This study was carried out from months June 2017 to July 2017. The results of the calculations from this study indicate that the total cost for one time jipang production reached Rp34.950.463, - per month, the average gain gained Rp133.554.450, -, while the calculation of R / C ratio of agro industry jipang Sinar Abadi shows the number> 1, which is 1.32. Jipang Agroindustry is declared worthy with value NPV Rp 979.900.978. Break Event Point Value (BEP), BEP receipt obtained value of Rp 474,425, BEP units obtained value of 12 Kg and BEP price obtained value of Rp 30,629, meaning do not experience any profit or loss before the age of the equipment ends. While Pay Back Period (PP) of 0.1 years, so it can be concluded that jipang agro industry Sinar Abadi is worth developing.